Current quarantine and suspension distances are excessive for incipient populations of Queensland fruit fly (Bactrocera tryoni (Froggatt)) (Diptera: Tephritidae) in southern New South Wales, Australia. (December 2020) - Dominiak, Bernard C.; Fanson, Benjamin G.
Abstract: The Queensland fruit fly (Qfly; Bactrocera tryoni Froggatt) is a major horticultural pest species in Australia and considered a serious quarantine concern, both domestically and internationally. When a Qfly outbreak is declared in the main horticultural regions of southeast Australia, a 15 km radius suspension zone is established (area of 707 km 2 ) around the epicentre of the outbreak. This suspension radius was originally adopted in the early 1990s. Here, we analysed trapping data in New South Wales (Australia) from 2002 to 2010 to evaluate the suitability of the 15 km suspension radius. There were 439 Qfly incursions recorded in Qfly-free zones, but only 9.9% of these incursions resulted in a declared outbreak. For these outbreaks, we conducted two distinct analyses. First, we modelled the distribution of infestation radii from the outbreaks and predicted the suspension distance using multiple levels of risk protection (e.g. probit 8.7, probit 9). Second, we fitted various probability distributions to individual fly trapping data and then estimated upper confidence limits for suspension distances, based on dispersal patterns of Qfly. Overall, the predicted suspension radii were substantially smaller than the current 15 km radius. Our results concur with other studies suggesting that Qfly are relatively poor colonisers. We propose that the current 15 km could be reduced substantially to 3 or 4 km. Highlights: Queensland fruit flies disperse much shorter distances compared to current perceptions. Generally, dispersal is much less than one kilometre. Current quarantine distances are excessive and result in needless disinfestation. Quarantine distances of 3–4 km are supported by the data.